The 3D shape of Type IIb SN 2011hs. Issue 1 (24th January 2019) - Stevance, H F; Maund, J R; Baade, D; Bruten, J; Cikota, A; Höflich, P; Wang, L; Wheeler, J C; Clocchiatti, A; Spyromilio, J; Patat, F; Yang, Y; et al.
Abstract: We observed seven epochs of spectropolarimetry in optical wavelengths for the Type IIb SN 2011hs, ranging from −3 to +40 d with respect to V -band maximum. A high degree of interstellar polarization was detected (up to ∼3 per cent), with a peak lying blueward of 4500 Å. Similar behaviours have been seen in some Type Ia supernovae (SNe), but had never been observed in a Type IIb. We find that it is most likely the result of a relative enhancement of small silicate grains in the vicinity of the SN. Significant intrinsic continuum polarization was recovered at −3 and +2 d ( p = 0.55 ± 0.12 per cent and 0.75 ± 0.11 per cent, respectively). We discuss the change of the polarization angle across spectral lines and in the continuum as diagnostics for the 3D structure of the ejecta. We see a gradual rotation by about −50° in the continuum polarization angle between −2 and +18 d after V -band maximum. A similar rotation in He i λ5876, Hα and the Ca ii infrared triplet seems to indicate a strong influence of the global geometry on the line polarization features. The differences in the evolution of their respective loops on the Stokes q − u plane suggest that line specific geometries are also being probed. Possible interpretations are discussed and placed in the context of literature. We find that the spectropolarimetry of SN 2011hs is most similar to that of SN 2011dh, albeit with notable differences.